Fbxw7 Tumor Suppressor: A Vital Regulator Contributes to Human Tumorigenesis - Cao, Jun (Medicine (Baltimore), 2016)
Rapidly accumulating data indicate that F-box/WD repeat-containing protein 7 (Fbxw7) is one of the most frequently mutated genes in human cancers and regulates a network of crucial oncoproteins. These studies have generated important new insights into tumorigenesis and may soon enable therapies targeting the Fbxw7 pathway. We searched PubMed, Embase, and ISI Web of Science databases (1973–2015, especially recent 5 years) for articles published in the English language using the key words “Fbxw7,” “Fbw7,” “hCDC4,” and “Sel-10,” and we reviewed recent developments in the search for Fbxw7. Fbxw7 coordinates the ubiquitin-dependent proteolysis of several critical cellular regulators, thereby controlling essential processes, such as cell cycle, differentiation, and apoptosis. Fbxw7 contains 3 isoforms (Fbxw7α, Fbxw7β, and Fbxw7γ), and they are differently regulated in subtract recognition. Besides those, Fbxw7 activity is controlled at different levels, resulting in specific and tunable regulation of the abundance and activity of its substrates in a variety of human solid tumor types, including glioma malignancy, nasopharyngeal carcinoma, osteosarcoma, melanoma as well as colorectal, lung, breast, gastric, liver, pancreatic, renal, prostate, endometrial, and esophageal cancers. Fbxw7 is strongly associated with tumorigenesis, and the mechanisms and consequences of Fbxw7 deregulation in cancers may soon enable the development of novel therapeutic approaches.